Risks Associated with the Market Behaviour of Bulgarian Industrial Enterprises - Ivanova, Z.S. (Економічний вісник Донбасу, 2015)
Bulgarian industrial enterprises operate in extremely competitive global markets. This inevitably increases the likelihood of the occurrence of a number of risks and increases their level of risk exposure. The purpose of this article is to highlight some of the main risks accompanying the demonstration of a certain market behaviour of Bulgarian industrial enterprises, to present the results of analyzing the risk exposure and the problem areas in their market behaviour, and to justify the opportunities for affecting the risks. Болгарські індустріальні підприємства функціонують в умовах виключної конкуренції глобальних ринків. Це безумовно збільшує ймовірність настання безлічі ризиків та збільшує ступінь впливу ризику. Ціль даної статті - виявити деякі з основних ризиків, що супутні демонстрації відповідної ринкової поведінки з боку болгарських індустріальних підприємств, надати результати аналізу впливу ризику та проблемні області їх ринкової поведінки, а також обґрунтувати можливості впливу на ризики. Болгарские индустриальные предприятия функционируют в условиях исключительной конкуренции глобальных рынков. Это неизбежно повышает вероятность наступления множества рисков и увеличивает их степень подверженности риску. Цель настоящей статьи - выявить некоторые из основных рисков, сопутствующих демонстрации определенного рыночного поведения со стороны болгарских индустриальных предприятий, представить результаты анализа подверженности риску и проблемные области их рыночного поведения, а также обосновать возможности воздействия на риски.